Inhibitory properties of ibuprofen and its amide analogues towards the hydrolysis and cyclooxygenation of the endocannabinoid anandamide. (February 2013) - Fowler, Christopher J.; Björklund, Emmelie; Lichtman, Aron H.; Naidu, Pattipati S.; Congiu, Cenzo; Onnis, Valentina
<x xml:space="preserve">Abstract</x> A dual-action cyclooxygenase (COX)–fatty acid amide hydrolase (FAAH) inhibitor may have therapeutic usefulness as an analgesic, but a key issue is finding the right balance of inhibitory effects. This can be done by the design of compounds exhibiting different FAAH/COX-inhibitory potencies. In the present study, eight ibuprofen analogues were investigated. Ibuprofen (1), 2-(4-Isobutylphenyl)-N-(2-(3-methylpyridin-2-ylamino)-2-oxoethyl)propanamide (9) and N-(3-methylpyridin-2-yl)-2-(4′-isobutylphenyl)propionamide (2) inhibited FAAH with IC50 values of 134, 3.6 and 0.52 µM respectively. The corresponding values for COX-1 were ~29, ~50 and ~60 µM, respectively. Using arachidonic acid as substrate, the compounds were weak inhibitors of COX-2. However, when anandamide was used as COX-2 substrate, potency increased, with approximate IC50 values of ~6, ~10 and ~19 µM, respectively. Compound 2 was confirmed to be active in vivo in a murine model of visceral nociception, but the effects of the compound were not blocked by CB receptor antagonists.